The virtue of industry-science collaborations - Dirk Czarnitzki (EIB Papers, 2009)
This article analyzes the potential benefits of industryscience collaborations for samples of Flemish and German firms. A firm collaborating with science may benefit from knowledge spillovers and public subsidies as industry-science collaborations are often granted preferred treatment. I shed light on the potential spillover and subsidy effects by estimating treatment effect models using nearest neighbour matching techniques. For both countries, I find positive effects on business R&D. Firms that engage in industryscience collaborations invest more in R&D compared to the counterfactual situation where they would not collaborate with science. Furthermore, within the sample of firms collaborating with science, a subsidy for that collaboration leads, on average, to higher R&D in the involved firms. Thus there is no full crowding-out of subsidies targeted to science-industry collaborations.
Keywords: 330; Forschungskooperation; Industrielle Forschung; Wissenstransfer; Forschungssubvention; Deutschland; Flandern